Manajemen Keluarga Terhadap Penanganan ISPA Berulang Pada Balita di Puskesmas Mangunsari Salatiga: Family Management Against Repeated Acute Respiratory Infections Handling In Toddlers at Mangunsari Salatiga Health Center - Fiane de Fretes; Sanfia Tesabela Messakh; Inel Dina Mariska Saogo (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
There are several factors that can cause ARI, one of which is the ability of the family to handle and prevent ARI. The purpose of this study is to find out and describe how family management in Salatiga is handling recurrent ARI in family members aged under five and respondent characteristics. This study uses a quantitative descriptive method with a cross sectional study design. Respondents involved were families with the criteria of having children under five who had recurrent ARI on average 2-3 times with data obtained from the Mangunsari Community Health Center in Salatiga. The results showed that all (50) respondents had good management in handling repetitive ARI based on the Integrated Toddler Disease Management Book Book (MTBS) by the Republic of Indonesia Ministry of Health in 2015 and sources of information obtained related to recurrent ARI as seen from the results of family knowledge aspects related to ARI as many as 49 (98%) families have good knowledge related to ARI and the management of recurrent ARI in infants carried out in the right way by all respondents. Handling of recurrent ARI in this study is the provision of symptomatic drugs, referral to the nearest health facility and rehabilitation at home. Based on the research results above, it can be concluded that family management in handling ARI over and over in infants at Mangunsari Salatiga Health Center is included in both categories which are assessed based on sources of information related to two aspects of research namely family knowledge related to ARI and early management of ARI over and over in infants